2002
DOI: 10.1111/j.1365-2621.2002.tb10321.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and Sensory Analysis of a Textured Whey Protein Meatless Patty

Abstract: Whey protein concentrate (WPC, 80% protein) was textured using thermoplastic extrusion to produce textured whey protein (TWP). Binding agents were investigated for their usefulness in the formation of a TWP meatless patty. Sensory analysis of 2 TWP patty formulations and a commercially available textured vegetable protein (TVP) patty was performed. Patties were evaluated on appearance, texture, flavor, aftertaste and overall acceptance. There were no significant differences among the appearance and texture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Even though starch is the primary ingredient in expanded breakfast cereals and snacks, addition of whey protein can enhance their nutritional value because their incorporation in extruded products may provide a nutritionally sound and economical approach to fortification (Allen et al 2007). Whey protein can be extruded into expanded products (Kim and Maga 1987;Sokhey et al 1996;Onwulata et al 1998;Walsh and Carpenter 2003;Liu et al 2006;Allen et al 2007) as well as fibrous-textured products (Hale et al 2002;Taylor and Walsh 2002;Walsh and Carpenter 2003;Walsh et al 2008). Undesirable effects of proteins extrusion include reduction of protein quality due to, e.g., the Maillard reaction, decrease in palatability, and loss of heat labile vitamins (Tran et al 2008).…”
Section: Introductionmentioning
confidence: 97%
“…Even though starch is the primary ingredient in expanded breakfast cereals and snacks, addition of whey protein can enhance their nutritional value because their incorporation in extruded products may provide a nutritionally sound and economical approach to fortification (Allen et al 2007). Whey protein can be extruded into expanded products (Kim and Maga 1987;Sokhey et al 1996;Onwulata et al 1998;Walsh and Carpenter 2003;Liu et al 2006;Allen et al 2007) as well as fibrous-textured products (Hale et al 2002;Taylor and Walsh 2002;Walsh and Carpenter 2003;Walsh et al 2008). Undesirable effects of proteins extrusion include reduction of protein quality due to, e.g., the Maillard reaction, decrease in palatability, and loss of heat labile vitamins (Tran et al 2008).…”
Section: Introductionmentioning
confidence: 97%
“…Rao et al, (1999 b) studied the effect of WPC on the quality of smoked chicken sausages from broiler spent hens and reported that frying loss of experimental smoked chicken sausage samples significantly reduced on addition of WPC. Meatless patties containing textured whey protein (WPC-80) with mushroom and vegetable flavour had similar acceptability as commercial soya patty (Taylor and Walsh, 2002).…”
Section: Whey Proteins In Infant Food Formulationmentioning
confidence: 99%
“…In one experiment, they texturized WPC by thermoplastic extrusion, rehydrated the fragments, and bound them into patties with wheat gluten, dehydrated egg whites, and xanthan gum (Taylor and Walsh, 2002). In one experiment, they texturized WPC by thermoplastic extrusion, rehydrated the fragments, and bound them into patties with wheat gluten, dehydrated egg whites, and xanthan gum (Taylor and Walsh, 2002).…”
Section: B Meat Analogs and Extendersmentioning
confidence: 99%